Help With Logarithm

PheelGoodInc

New member
Joined
May 20, 2015
Messages
3
Hi, thanks for having me on the site. I'm reviewing for a test and am stuck on two logarithms.

logarithms.JPG

The two in question are highlighted aboce.

Number 16, I keep trying to raise 2x^2+3? I'm getting nowhere with that and google hasn't helped much. (it's much harder to search google for logarithm problems due to the format of the text).

Number 19, I have tried cancelling the logs since they have the same bse.

I get 2x-8=20
Simplified to 12. The answer sheet says it's 10.

Any help is greatly appreciated. Thank you.
 
Hi, thanks for having me on the site. I'm reviewing for a test and am stuck on two logarithms.

View attachment 5329

The two in question are highlighted aboce.

Number 16, I keep trying to raise 2x^2+3? I'm getting nowhere with that and google hasn't helped much. (it's much harder to search google for logarithm problems due to the format of the text).

Number 19, I have tried cancelling the logs since they have the same bse.

I get 2x-8=20
Simplified to 12. The answer sheet says it's 10.

Any help is greatly appreciated. Thank you.

(18)

\(\displaystyle \displaystyle{2^{x^2}\cdot 8 \ = \ 4^{2x}}\) →

\(\displaystyle \displaystyle{\ 2^{x^2}\cdot 2^3 \ = \ 4^{2x}}\)→

\(\displaystyle \displaystyle{\ 2^{x^2 + 3} \ = \ (2^2)^{2x}}\)→

\(\displaystyle \displaystyle{\ 2^{x^2 + 3} \ = \ 2^{4x}}\)→

Continue....

(19)

\(\displaystyle \displaystyle{2Log_{11}(x-4) \ = \ Log_{11}2 + Log_{11}18}\)→

\(\displaystyle \displaystyle{Log_{11}[(x-4)^2] \ = \ Log_{11}(2*18)}\)→

\(\displaystyle \displaystyle{Log_{11}[(x-4)^2] \ = \ Log_{11}(36)}\)→ Now you can eliminate "Log"s.
 
Last edited by a moderator:
Hi, thanks for having me on the site. I'm reviewing for a test and am stuck on two logarithms.

View attachment 5329

The two in question are highlighted aboce.

Number 16, I keep trying to raise 2x^2+3? I'm getting nowhere with that and google hasn't helped much. (it's much harder to search google for logarithm problems due to the format of the text).

Number 19, I have tried cancelling the logs since they have the same bse.

I get 2x-8=20
Simplified to 12. The answer sheet says it's 10.

Any help is greatly appreciated. Thank you.

Just a different way for (18)
\(\displaystyle 2^{x^2}\, 8\, =\, 4^{2x}\, \Rightarrow\, ln_2(2^{x^2}\, 8)\, =\, ln_2(4^{2x})\, \Rightarrow\)
\(\displaystyle ln(2^{x^2})\, +\, ln_2(8)\, =\, {2x}\, ln_2(4)\Rightarrow\, ...\)
 
Just a different way for (18)
\(\displaystyle 2^{x^2}\, 8\, =\, 4^{2x}\, \Rightarrow\, ln_2(2^{x^2}\, 8)\, =\, ln_2(4^{2x})\, \Rightarrow\)
\(\displaystyle ln(2^{x^2})\, +\, ln_2(8)\, =\, {2x}\, ln_2(4)\Rightarrow\, ...\)

"ln" looks like the abbreviation for natural log. And there is a "sub 2" missing from left side of the bottom equation.


The use of \(\displaystyle \ log_2 \ \) makes it clear.

OP, this is actually problem # 16.


\(\displaystyle \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 2^{x^2}*8 \ = \ 4^{2x} \ \implies\)

\(\displaystyle \ \ \ \ \ \ \ \ \ \ \ \ \log_2(2^{x^2}*8) \ = \ \log_2(4^{2x}) \ \implies\)

\(\displaystyle \log_2(2^{x^2}) + \log_2(8) \ = \ \log_2(4^{2x}) \ \implies\)

\(\displaystyle \log_2(2^{x^2}) + \log_2(2^3) \ = \ \log_2[(2^2)^{2x}] \ \implies\)

\(\displaystyle \log_2(2^{x^2}) + \log_2(2^3) \ = \ \log_2(2^{4x}) \ \implies\)

\(\displaystyle \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x^2 + 3 \ = \ 4x \ \implies \ \ \) ?
 
"ln" looks like the abbreviation for natural log. And there is a "sub 2" missing from left side of the bottom equation.


The use of \(\displaystyle \ log_2 \ \) makes it clear.

OP, this is actually problem # 16.


\(\displaystyle \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 2^{x^2}*8 \ = \ 4^{2x} \ \implies\)

\(\displaystyle \ \ \ \ \ \ \ \ \ \ \ \ \log_2(2^{x^2}*8) \ = \ \log_2(4^{2x}) \ \implies\)

\(\displaystyle \log_2(2^{x^2}) + \log_2(8) \ = \ \log_2(4^{2x}) \ \implies\)

\(\displaystyle \log_2(2^{x^2}) + \log_2(2^3) \ = \ \log_2[(2^2)^{2x}] \ \implies\)

\(\displaystyle \log_2(2^{x^2}) + \log_2(2^3) \ = \ \log_2(2^{4x}) \ \implies\)

\(\displaystyle \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x^2 + 3 \ = \ 4x \ \implies \ \ \) ?

Answer sheet has it as (1,3). How is that?
 
Also, the answer sheet has 10 for number 19. I'm not even close.

Use Subhotosh Khan's suggestion to eliminate the \(\displaystyle log_{11}\). That will give you a quadratic. One of the roots is "a false root introduced by squaring the (x-4)", so check both roots with the original equality.

For example, suppose I have
x - 4 = 6
then
(x - 4)2 = 36
If I use just the second equality, x can be either -2 or +10 and, by checking back with the original equation, we see than x=10 is the proper solution. Now, if the original equation had been
|x - 4| = 6
then both solutions would be correct.
 
Top